Determination of the Model Basis for Assessing the Vehicle Energy Efficiency in Urban Traffic - Miroslaw Śmieszek; Nataliia Kostian; Vasyl Mateichyk; Jakub Mościszewski; Liudmyla Tarandushka (Energies, 2021)
The paper studies the problem of assessing the vehicle energy efficiency on the streets of urban road network. As a result of morphological analysis of the system “Vehicle—Traffic flow—Road—Traffic Environment” 18 significant morphological attributes of its functional elements, that affect the energy efficiency of vehicles, were identified. Each attribute is characterized by 3–6 implementation variants, which are evaluated by the relevant quantitative or qualitative parameters. The energy efficiency of vehicles is determined by the criteria of their energy consumption considering the vehicle category, type of energy unit, mode of vehicle movement and adjustment factors—road, climatic and others. The input parameters values of the system in the process of traffic flow on the linear fragments of streets and road networks of the cities of Ukraine and Poland were measured. The set of independent system parameters is determined by applying the Farrar-Glober method based on statistical estimates. The specified set is the basis of the studied system and is formed of 10 independent input parameters. The presence in the basis of parameters that correspond to the morphological features of all four functional elements, confirmed the importance of these elements of the system. The mathematical dependence of the impact of vehicle characteristics, traffic flow, road and environment on vehicle energy efficiency is built. The standard deviation of the model values from the tabular ones equals <semantics><mover>σ´</mover>=0.0091</semantics>. Relative standard deviation equals <semantics><mover>S´</mover>r=1.5%</semantics>. The results of the study could be used in the development of new and optimization of existing intelligent traffic control systems of urban transport.